Answer:
-6
Step-by-step explanation:
We are given x=- 3 , y= 6 and z= -4.
We are also given the expression:
-15 + (-x) +y
Substitute -3 in for x and 6 in for y.
-15 + (- -3) + 6
2 negative signs creates a positive sign
-15 + (+3) +6
-15 + 3+ 6
Add -15 and 3.
(-15+3) +6
-12 +6
Add -12 and 6.
-6
-15+(-x)+y evaluated at x= -3 and y=6 is equal to -6.
A ray is a defined term because it has no width or depth is described using an undefined term has an informal definition travels forever in one way
Answer:
True
Step-by-step explanation:
Quadratic equations have the highest degree on x as 2. The given equation has 3x^2, meaning that it is quadratic.
<u>ANSWER:
</u>
The total cost of the skate board is $74.61.
<u>SOLUTION:
</u>
Given, Luis wants to buy a skateboard that usually sells for $79.99. all merchandise is discounted by 12%. luis has to pay a state sales tax of 6.75%.
We need to find what is the total cost of the skateboard.
Final cost is nothing but original amount subtracted by discount and added with tax.
final cost = original cost – discount + sales tax
Original cost = $79.99
Discount = 12% of original cost
![\begin{array}{l}{=12 \% \times 79.99} \\\\ {=\frac{12}{100} \times 79.99} \\\\ {=\frac{959.88}{100}} \\\\ {=9.5988}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%3D12%20%5C%25%20%5Ctimes%2079.99%7D%20%5C%5C%5C%5C%20%7B%3D%5Cfrac%7B12%7D%7B100%7D%20%5Ctimes%2079.99%7D%20%5C%5C%5C%5C%20%7B%3D%5Cfrac%7B959.88%7D%7B100%7D%7D%20%5C%5C%5C%5C%20%7B%3D9.5988%7D%5Cend%7Barray%7D)
discount is $9.6 approximately
Sales tax = 6% of cost after discounting
![\begin{array}{l}{=6 \% \times \text { (original cost - discount) }} \\\\ {=\frac{6}{100} \times(79.99-9.6)} \\\\ {=\frac{6}{100} \times(70.39)} \\\\ {=\frac{422.34}{100}} \\\\ {=4.2234}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%3D6%20%5C%25%20%5Ctimes%20%5Ctext%20%7B%20%28original%20cost%20-%20discount%29%20%7D%7D%20%5C%5C%5C%5C%20%7B%3D%5Cfrac%7B6%7D%7B100%7D%20%5Ctimes%2879.99-9.6%29%7D%20%5C%5C%5C%5C%20%7B%3D%5Cfrac%7B6%7D%7B100%7D%20%5Ctimes%2870.39%29%7D%20%5C%5C%5C%5C%20%7B%3D%5Cfrac%7B422.34%7D%7B100%7D%7D%20%5C%5C%5C%5C%20%7B%3D4.2234%7D%5Cend%7Barray%7D)
Sales tax is $4.22 approximately
Now, final cost = 79.99 – 9.6 + 4.22
= 84.21 - 9.6
= 74.61
Hence, the total cost of the skate board is $74.61
Answer:
The average rate of change for f(x) from x=−1 to x = 4 is, 1
Step-by-step explanation:
Average rate A(x) of change for a function f(x) over [a, b] is given by:
![A(x) = \frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
As per the statement:
![f(x) = x^2-2x-4](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2-2x-4)
we have to find the average rate of change from x = -1 to x = 4
At x = -1
![f(-1) = (-1)^2-2(-1)-4 = 1+2-4 = -1](https://tex.z-dn.net/?f=f%28-1%29%20%3D%20%28-1%29%5E2-2%28-1%29-4%20%3D%201%2B2-4%20%3D%20-1)
and
at x = 4
![f(4) = (4)^2-2(4)-4 = 16-8-4 = 4](https://tex.z-dn.net/?f=f%284%29%20%3D%20%284%29%5E2-2%284%29-4%20%3D%2016-8-4%20%3D%204)
Substitute these in [1] we have;
![A(x) = \frac{f(4)-f(-1)}{4-(-1)}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%284%29-f%28-1%29%7D%7B4-%28-1%29%7D)
⇒![A(x) = \frac{4-(-1)}{4+1}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7B4-%28-1%29%7D%7B4%2B1%7D)
⇒![A(x) = \frac{5}{5}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7B5%7D%7B5%7D)
Simplify:
A(x) = 1
Therefore, the average rate of change for f(x) from x=−1 to x = 4 is, 1